"Filhos de abrigo": adoção tardia de crianças no Espírito Santo, 2009-2019 - Mergar, Stella Scantamburlo de (2020)
Considering the studies on the childhood and children adoption, this dissertation investigates the hypothesis that children over 06 years old are ignored, stigmatized for their ages on adoptive processes. For the analysis, we consider determinant the social representations built concerning the family, motherhood and childhood, promoting the valuation of early childhood and biological bonds. To explore the adoption situation in Brazil, it was used the inductive method, starting from private data, duly verified, and inferring a general truth, before not existent on examined parties. Therefore, it were gather quantitative data referent to children and teenagers, at national, state and municipal levels (the two last levels limited to the state of Espírito Santo), from the National Adoption Register (Cadastro Nacional de Adoção – CNA) and the new National Adoption and Reception System (Sistema Nacional de Adoção e Acolhimento – SNA). Semi-structured interviews were conducted with five adoption applicants judicially registered, used to point out possibilities regarding the statistical data of adoption existing in Brazil. This study’s spatial cut was limited to the state of Espírito Santo, and its temporal cut, from 2009 to 2019, when the Legislation nº 12.010/2009 (National Adoption Law – Lei Nacional da Adoção), which implemented important changes on the Legislation nº 8.069/1990 (Child and Adolescent Statute – Estatuto da Criança e do Adolescente), such as the regulation of the extraordinary and irrevocable condition of the adoption, the determination of a preparatory period of coexistence and the strengthening of biological bonds by prioritizing the child’s stay with the natural family, completed 10 years of existence. The narratives, altogether with the gathered data, indicated to the individual’s need of experience the child’s early childhood and the belief on the possibility of preexistent habits and mischievous behaviors. Besides that, we verified a great influence from the social and cultural environment we are inserted, and so, given the circumstances of each era, the early childhood was valued to enable the children’s survival and, afterwards, went on to the stigmatization of poor childhood, understood as a synonym for delinquency